Future of battery thermal management systems (BTMS): Role of advanced technologies, artificial intelligence and sustainability - Quazi, Moinuddin Mohammed; Jaliliantabar, Farzad; Sudhakar, Kumarasamy; Ezazi, Mohammadamin (Elsevier Ltd, 2025)
The research in battery thermal management systems (BTMS) eventually transforms from well-established conventional techniques through hybrid approaches towards smart and innovative changeover. This is only plausible thanks to researchers' imminent focus towards including artificial intelligence (AI), smart materials, and sustainable approaches in BTMS. This article provides a current understanding of AI models, approaches, and techniques employed to predict the battery's state, failure conditions, high-stress scenarios and thermal behaviour, including maximum and minimum temperatures. The pros and cons of various AI technology and methods are examined. This is followed by a detailed review of emerging advanced technologies such as additive manufacturing to develop customized cooling channels, optimized structures, bioinspired BTMS to improve thermal behaviours, and smart materials for all weather, both heating and cooling solutions. The mist-based cooling system for hazard mitigation is another emerging area for thermal runaway prevention that is reviewed. Lastly, the role of sustainability in technological, socioeconomic, environmental, and cost-effective measures is also discussed. Finally, the potential directions and key points for the future development of battery thermal management systems for a wide range of operation conditions that prevent thermal runaway and safety mitigation systems are also proposed.